Determination of Hydroxycitric Acid (HCA) content in Roselle (Hibiscus sabdariffa L.) through extraction of Potassium Hydroxycitrate and High Performance Liquid Chromatography (HPLC) - Halimaton Saadiah Othman (Universiti Sains Islam Malaysia, 2024)
Thesis (M.Sc)-- Faculty of Science and Technology, Universiti Sains Islam Malaysia, 2011